Livros didáticos de geografia e seus autores: uma análise contextualizada das décadas de 1870 a 1910, no Brasil - Angelo, Maria Deusia Lima (2014)
Geography has always been present since the first schools established in Brazil, however it‟s history as school knowledge still little known, even if that issue is taking place nowadays. Aiming contribute to the research in the history of scholar geography, this work intends to highlight elements that allow us to think about the constitution process of the discipline in the Brazilian school context, between the 1870‟s and 1910‟s. Therefore, our analyzes were directed to Geography textbooks and to the persons responsible to elaborate such works, focusing on the authors. As a theoretical-methodological perspective, we rely on the history of school subjects, besides resorting to important representative elements of the field of school culture, of the social history and of the history of the book, among other contributions. The temporal context portrayed in this study includes important changes in various sectors of brazilian society, gaining centrality the republican and nationalist ideas. In the educational sector, it becomes clear an expansion of schooling, particularly in primary schools, covering various parts of the country, culminating in increased production of textbooks. Our survey on the Geography textbooks expressed a fertility of production, resulting in a total of 186 books, written by 134 authors, including works for regional geography. The books for use in schools in general comprise 134 titles, demonstrating a greater number of publications aimed at secondary school, instead of primary education. In reference to the works of regional geography, we cataloged a total of 52 books. In this case, considering the two levels of education mentioned, we observed a greater expressiveness for primary education. As for the number of authors, we have identified a heterogeneity of subjects coming from different provinces / states, with different backgrounds and performances. The highlights were the authors who performed the activity of teaching and those related to scientific and cultural institutions of the period, for example, those from the IHG.